Philippine journalism handbook - Ramirez, Jaime B. (Metro Manila National Book Store, 1989)
Purpose: "It's primary goal is to bring to open the different aspects and problems of the noble profession so that future journalists will be able to make their way on the desk of a newspaper anywhere."
Content/s: The Philippine Press. Free press and National development. Journalism as a career. Student press. Print media. Print media organization. Feature writing. Investigative writing. Economic news writing. Foreign news writing in the third world. Newspaper Column. Press photography. Code of Ethics. The New Media.
Fi-10705g donated by Prof. mamoru tsuda, M.A.,U.P.,1977.
Keywords: Journalism -- Philippines; Journalism -- Handbooks, manuals, etc